Sulfammox in sediments of a natural wetland in northeastern Mexico: a sustainable approach to nitrogen and sulfur removal - Ricardo Romero-Arguelles; Mayra A. Gómez-Govea; Aylin E. Adame-Martinez; Antonio Guzman-Velazco; José I. Gonzalez-Rojas; José G. Ham-Dueñas; Hector J. Amezquita-Garcia; E. Emilia Rios-Del Toro (Science of The Total Environment, 2025)

Dietary vitamin D intake and 2-year changes in cognitive function in older adults with overweight or obesity and metabolic syndrome - Héctor Vázquez-Lorente; Jiaqi Ni; Indira Paz-Graniel; Estefanía Toledo; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (GeroScience, 2025)
The protective role of dietary vitamin D intake on cognitive function is of interest, but evidence remains inconsistent. We aimed to evaluate the association between dietary vitamin D intake and 2-year cognitive changes in older adults at risk of cognitive decline. This longitudinal study comprised 5454 individuals (aged 55–75 years in men and 60–75 years in women) who exhibited overweight/obesity and metabolic syndrome. Data on dietary vitamin D intake was assessed using a validated 143-item food frequency questionnaire. Cognitive function was assessed through five composite scores derived from a comprehensive battery of eight neuropsychological tests, encompassing global cognitive function, general cognitive function, attention, executive function, and language domains. Multivariable-adjusted linear regression models were fitted to examine the association between energy-adjusted cumulative average dietary vitamin D intake over time and 2-year changes in cognitive function. After adjusting for multiple covariates, energy-adjusted cumulative average dietary vitamin D intake as a continuous variable was associated with greater 2-year improvements in global cognitive function ( β 1.18 × 10 −2 ; 95% CI 0.19 × 10 −2 to 2.17 × 10 −2 ), executive function ( β 1.12 × 10 −2 ; 95% CI 0.03 × 10 −2 to 2.21 × 10 −2 ), and language ( β 1.61 × 10 −2 ; 95% CI 0.43 × 10 −2 to 2.78 × 10 −2 ). Additionally, the higher cumulative average dietary vitamin D intake quartile was associated with an increase in global cognitive function ( β 7.10 × 10 −2 ; 95% CI 0.59 × 10 −2 to 13.6 × 10 −2 ), language ( β 7.07 × 10 −2 ; 95% CI − 0.52 × 10 −2 to 14.7 × 10 −2 ), and a lower decline in attention ( β 9.58 × 10 −2 ; 95% CI 1.60 × 10 −2 to 17.5 × 10 −2 ). A higher dietary vitamin D intake was associated with modest favorable changes in cognitive function and a reduced cognitive decline over a 2-year period. These findings highlight the need for further research to explore the potential benefits of boosting dietary vitamin D intake for cognitive health in older adults.

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Ultra-processed foods consumption as a promoting factor of greenhouse gas emissions, water, energy, and land use: A longitudinal assessment - Silvia García; Rosario Pastor; Margalida Monserrat-Mesquida; Laura Álvarez-Álvarez; María Rubín-García; Miguel Ángel Martínez-González; Jordi Salas-Salvadó; Dolores Corella; Montserrat Fitó; J. Alfredo Martínez; Lucas Tojal-Sierra; Julia Wärnberg; et al. (Science of The Total Environment, 2023)

Dietary intake of polychlorinated dibenzo-p-dioxins and furans, adiposity and obesity status. - Nadine Khoury; María Ángeles Martínez; Indira Paz-Graniel; Miguel Ángel Martínez-González; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (Environmental Research, 2023)

Monitoring Black Sea environmental changes from space: New products for altimetry, ocean colour and salinity. Potentialities and requirements for a dedicated in-situ observing system - Marilaure Grégoire; Aida Alvera-Azcaráte; Luminita Buga; Arthur Capet; Sorin Constantin; Fabrizio D’ortenzio; David Doxaran; Yannis Faugeras; Aina Garcia-Espriu; Mariana Golumbeanu; Cristina González-Haro; Verónica González-Gambau; et al. (Frontiers in Marine Science, 2023)
In this paper, satellite products developed during the Earth Observation for Science and Innovation in the Black Sea (EO4SIBS) ESA project are presented. Ocean colour, sea level anomaly and sea surface salinity datasets are produced for the last decade and validated with regional in-situ observations. New data processing is tested to appropriately tackle the Black Sea’s particular configuration and geophysical characteristics. For altimetry, the full rate (20Hz) altimeter measurements from Cryosat-2 and Sentinel-3A are processed to deliver a 5Hz along-track product. This product is combined with existing 1Hz product to produce gridded datasets for the sea level anomaly, mean dynamic topography, geostrophic currents. This new set of altimetry gridded products offers a better definition of the main Black Sea current, a more accurate reconstruction and characterization of eddies structure, in particular, in coastal areas, and improves the observable wavelength by a factor of 1.6. The EO4SIBS sea surface salinity from SMOS is the first satellite product for salinity in the Black Sea. Specific data treatments are applied to remedy the issue of land-sea and radio frequency interference contamination and to adapt the dielectric constant model to the low salinity and cold waters of the Black Sea. The quality of the SMOS products is assessed and shows a significant improvement from Level-2 to Level -3 and Level-4 products. Level-4 products accuracy is 0.4-0.6 psu, a comparable value to that in the Mediterranean Sea. On average SMOS sea surface salinity is lower than salinity measured by Argo floats, with a larger error in the eastern basin. The adequacy of SMOS SSS to reproduce the spatial characteristics of the Black Sea surface salinity and, in particular, plume patterns is analyzed. For ocean colour, chlorophyll-a, turbidity and suspended particulate materials are proposed using regional calibrated algorithms and satellite data provided by OLCI sensor onboard Sentinel-3 mission. The seasonal cycle of ocean colour products is described and a water classification scheme is proposed. The development of these three types of products has suffered from important in-situ data gaps that hinder a sound calibration of the algorithms and a proper assessment of the datasets quality. We propose recommendations for improving the in-situ observing system that will support the development of satellite products.

Expression of miR-34a and miR-15b during the progression of cervical cancer in a murine model expressing the HPV16 E7 oncoprotein - Rodolfo Ocadiz-Delgado; Jose-Luis Cruz-Colin; Elizabeth Alvarez-Rios; Antonio Torres-Carrillo; Karina Hernandez-Mendoza; Juan-Cristobal Conde-Pérezprina; Guadalupe-Isabel Dominguez-Gomez; Enrique Garcia-Villa; Paul F. Lambert; Patricio Gariglio (Journal of Physiology and Biochemistry, 2021)

Mediterranean Diet and Cardiovascular Risk: Beyond Traditional Risk Factors - Javier Delgado-Lista; Pablo Perez-Martinez; Antonio Garcia-Rios; Ana I. Perez-Caballero; Francisco Perez-Jimenez; Jose Lopez-Miranda (Critical Reviews in Food Science and Nutrition, 2016)

Spatial distribution and concentration assessment of total petroleum hydrocarbons in the intertidal zone surface sediment of Todos os Santos Bay, Brazil - Carine S. Silva; Icaro T. A. Moreira; Olivia M. C. de Oliveira; Antonio F. S. Queiroz; Karina S. Garcia; Brunno A. Falcão; Narayana F. C. Escobar; Mariana Cruz Rios (Environmental Monitoring and Assessment, 2014)